DEVELOPMENT AND DISPLACEMENT IN KERALA: AN EXPERIENCE OF COCHIN INTERNATIONAL AIRPORT LIMITED (CIAL) - T.V., Aneesh; Patil, R.R. (European Scientific Journal, ESJ, 2015)
The India has adopted new economic policy as well as structural adjustment programmes after 1991 to compete at the International market, the process of restructuring its old model development to new initiatives of Liberalization, Privatisation and Globalization also started in Kerala. The ‘Kerala model of development’ is widely known as the simultaneous persistence of high social development and lowest economic growth. It is a classic example of continuous debate on the phenomenon of "lopsided development" which means highest social development with stagnant economic growth. Although many scholars have criticised Kerala model as development replica for other Indian states due to its slow economic growth (Subrahmanian, 2006). It is in this context, the paper takes overview of Kerala model of development and impact of economic reform by examining the developmental projects and the outgrowing displacement in the name of development in the state of Kerala. The research paper examines the land acquisition and displacement in Kerala by taking case of Cochin International Airport Limited (CIAL) to understand the perception and experience of development in post reform era. The paper is based on descriptive research design, adopting snow ball sampling technique to identify the project affected people(PAP) in two resettlement colony of Ernakulam district of Kerala and total 50 sample size of PAP households have been used for data collection purpose and data have been quantitatively analysed to understand the impact of CIAL on the PAP. The findings of the study reveal that CIAL has created multi-dimensional impact on the PAP and the rehabilitation and resettlement still remains unresolved issues for the affected population.